Substrate Integrated Waveguide Filters Based on Even- And Odd- Mode Predistortion Technique - Zakaria, Zahriladha; Hunter, Ian (Penerbit Universiti, UTeM, 2011)
Novel techniques for the design of predistorted Substrate Integrated Waveguide (SIW) bandpass and bandstop filter are presented. The techniques allow for the realization of lossy filters with ideal lossless transmission and reflection response, offset by a constant amount. Two prototype third-degree Chebyshev bandpass and Inverse Chebyshev bandstop filters are proposed and designed. The two SIW filters having the same center frequency of 6.5 GHz and bandwidth of 125 MHz are implemented on RT/Duroid 4350 substrate with thickness of 0.508 mm. Experimental results show excellent agreement with simulated performance. These new class of filters would be useful in microwave systems where the increased insertion loss can be tolerated, such as in a satellite IMUX.